NON PERFORMING FINANCING OF BUYING AND SELLING FINANCING SCHEMES ISLAMIC BANKING IN INDONESIA : DURING AND AFTER THE COVID 19 PANDEMIC - Fauziyah, Fauziyah; Kurniawan, Widiar Onny; Hariawan, Ferry; Afkar, Taudlikhul; Utomo, Sigit Prihanto; Alviansyah, Redondo; Agustin, Fannisa Putri (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2024)
Non-performing financing is a problem for every sharia financial institution that distributes financing to customers who are the result of failure to pay. This research aims to conduct a test of the difference between non-performing financing from buying and selling financing, namely murabahah and istishna' Islamic Bank in Indonesia during the covid-19 pandemic and after the covid-19 pandemic. The research method used is quantitative research with consideration of generalizing the research results into a more general form so that it is easy to understand. The population in this study is 14 Sharia Commercial Banks, which are also used as a sample for this research. The sampling technique used in this study is the Saturated sample technique by using all the populations as samples because the number is relatively small with the consideration that all samples are considered homogeneous in the distribution of the data used. The data used is the combined financial statements of 14 Sharia Commercial Banks in Indonesia with the division of data for 2020-2021 as data during the Covid-19 pandemic, while the data for 2022-2023 is data after the Covid-19 pandemic. The data analysis technique used in this study is a paired sample t-test which is used to conduct a differential test of non-performing financing from murabahah financing and istishna financing. The findings of this research show that non-performing financing murabahah financing shows a difference with a tendency to increase. Meanwhile, non-performing financing of istishna financing shows a difference with a tendency to decrease